Pembekalan Pengetahuan Dan Keterampilan Kuliner Ikan Berbasis Wisata Pantai Di Dusun Lamangkia Desa Topejawa - Buana Basir; Nuraeni L. Rapi; Mutemainna Karim; Mesalina Tri Hidayani; Harianti Harianti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Topejawa village has the potential to develop a fish culinary business. The coastline that stretches as far as 0.8 km and the existence of fish landing sites (TPI) in the Lamangkia Topejawa Hamlet are very possible for the community to create a fish culinary business that is integrated with the Lamangkia coastal tourism area. The purpose of the activity is to empower the community for fish culinary business and it is hoped that it can help in improving the standard of living of the people of Dusun Lamangkia. The method of carrying out activities is by carrying out social approaches. The approach is carried out through outreach activities, counseling on the processing of fishery products, training and technical guidance on processing, assistance in establishing and legalizing businesses, as well as assistance in the manufacture of business products. The results of the implementation of the activity are the creation of motivation to carry out a fish-based processing business, as well as the formation of the Mentari Lamangkia fish culinary business